2020
DOI: 10.1038/s41598-020-63534-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the operating factors controlling Kouleothrix (type 1851), the dominant filamentous bacterial population, in a full-scale A2O plant

Abstract: This study reveals that the abundance of the filament Kouleothrix (Eikelboom type 1851) correlated positively with poor settleability of activated sludge biomass in a Japanese full-scale nutrient removal wastewater treatment plant sampled over a one-year period. 16S rRNA amplicon sequence data confirmed that Kouleothrix was the dominant filament in the plant, with a relative abundance of 3.06% positively correlated with sludge volume index (SVI) (R = 0.691). Moreover, Kouleothrix (type 1851) appeared to form i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…It is reported that Thermoanaerobacterium have strong resistance against UV light, heavy metals, and oxidative stress ( Rosenberg et al, 2014 ), thus the highest relative abundance of Thermoanaerobacterium in the present study was found in DH. Different from the biocrusts in drylands, filamentous bacterium Kouleothrix , the main filamentous bacteria for sludge bulking in sewage treatment plants ( Nittami et al, 2019 , 2020 ), was also found in this study, and this may be ascribed to the geographical location of this gold mine.…”
Section: Discussioncontrasting
confidence: 49%
“…It is reported that Thermoanaerobacterium have strong resistance against UV light, heavy metals, and oxidative stress ( Rosenberg et al, 2014 ), thus the highest relative abundance of Thermoanaerobacterium in the present study was found in DH. Different from the biocrusts in drylands, filamentous bacterium Kouleothrix , the main filamentous bacteria for sludge bulking in sewage treatment plants ( Nittami et al, 2019 , 2020 ), was also found in this study, and this may be ascribed to the geographical location of this gold mine.…”
Section: Discussioncontrasting
confidence: 49%
“…2020b; Nittami et al . 2020), and previously undefined filaments have been described by comparing corresponding changes in their relative abundances. For example, Trichococcus (Wang et al .…”
Section: Quantification Of Filamentous Bacteriamentioning
confidence: 99%
“…2018), Japan (Nittami et al . 2020), Singapore (Guo and Zhang 2012), and United States (Guo and Zhang 2012), usually where plant samples are collected regularly (each week) from the same plant at regular intervals, and populations identified using appropriate data bases. Of these, the MiDAS version 2/3 database (designed especially for wastewater plant communities (McIlroy et al .…”
Section: Filament Biogeography‐ Global/national Occurrence Of Bulking...mentioning
confidence: 99%
See 1 more Smart Citation
“…The main filamentous genera found were Thiothrix and Kouleothrix. Both organisms have been associated with serious bulking problems in (industrial) activated sludge plants (Nielsen et al 2000;Nittami et al 2020).…”
Section: Lab-scale Testingmentioning
confidence: 99%